2017
DOI: 10.1038/ngeo2912
|View full text |Cite
|
Sign up to set email alerts
|

Smaller desert dust cooling effect estimated from analysis of dust size and abundance

Abstract: (2017), Smaller desert dust cooling effect estimated from analysis of desert dust size and abundance, Nature Geoscience,10,[274][275][276][277][278] Desert dust aerosols affect Earth's global energy balance through direct interactions with radiation, and through indirect interactions with clouds and ecosystems. But the magnitudes of these effects are so uncertain that it remains unclear whether atmospheric dust has a net warming or cooling effect on global climate. Consequently, it is still uncertain whether l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

47
620
5
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 413 publications
(673 citation statements)
references
References 76 publications
47
620
5
1
Order By: Relevance
“…In their overview and review paper, the authors stated that the dust extinction coefficient and the corresponding dust AOT-related radiative effects are sensitively controlled by the amount of occurring fine dust particles due to their higher extinction efficiency, whereas coarse dust dominates the surface concentration, deposition, and removal. In a recent study, Kok et al (2017) emphasize in detail the consequences of a not-well-modeled dust size distribution and abundance for the global energy balance through direct interaction of dust with radiation. As mentioned, the indirect climate effect of dust through interaction with clouds is also affected if the dust size distribution and load, and thus estimates of CCN and INP concentrations are wrong in the forecast models.…”
Section: Fine-mode and Coarse-mode Dust Profiles: Simulation Vs Obsementioning
confidence: 99%
See 2 more Smart Citations
“…In their overview and review paper, the authors stated that the dust extinction coefficient and the corresponding dust AOT-related radiative effects are sensitively controlled by the amount of occurring fine dust particles due to their higher extinction efficiency, whereas coarse dust dominates the surface concentration, deposition, and removal. In a recent study, Kok et al (2017) emphasize in detail the consequences of a not-well-modeled dust size distribution and abundance for the global energy balance through direct interaction of dust with radiation. As mentioned, the indirect climate effect of dust through interaction with clouds is also affected if the dust size distribution and load, and thus estimates of CCN and INP concentrations are wrong in the forecast models.…”
Section: Fine-mode and Coarse-mode Dust Profiles: Simulation Vs Obsementioning
confidence: 99%
“…Gravitational settling also sensitively depends on the simulated fine and coarse dust fractions. The same holds for dust radiative effects which are rather different for fine and coarse dust particles (Nabat et al, 2012;Ridley et al, 2016;Kok et al, 2017). Meanwhile, dust simulations are also used to estimate dust ice-nucleating particle (INP) concentrations (Hande et al, 2015;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atmospheric dust has been observed across continents and oceans, giving rise to its importance in both terrestrial and marine ecosystems (Huebert et al, 2003;Mahowald et al, 2009;IPCC, 2013;Kok et al, 2017). Mineral aerosols can influence air quality by reducing visibility and bolstering concentrations of inhalable particulate matter (Sharratt and Lauer, 2006;Huneeus et al, 2011;Goudie, 2014).…”
mentioning
confidence: 99%
“…In addition, laboratory studies have suggested that the internal mixing state, particularly metal oxide -clay mineral assemblages, has important influence on radiative properties of dust (Nousiainen et al, 2009;Jeong and Nousiainen, 2014;Kemppinen et al, 2015;Di Biagio et al, 2017;Caponi et al, 2017). This highlights the need for measurement of single particle composition, including both mineralogy and internal mixing state in order to 20 provide better constraints for global climate models (Kok et al, 2017). …”
mentioning
confidence: 99%